THE ROLE OF GAMIFICATION IN TEACHING ENGLISH (Web of Teachers: Inderscience Research, 2025)
This study explores the role of gamification in teaching English and examines how game-based elements can enhance learners’ motivation, engagement, and language proficiency. Drawing on recent research and classroom practices, the paper analyzes key gamification components such as points, badges, levels, challenges, and immediate feedback. The findings suggest that integrating these elements into English lessons encourages active participation, supports sustained attention, and promotes autonomous learning. Moreover, gamification helps create a positive learning environment where learners feel safe to experiment, make mistakes, and improve through repetition. However, the study also highlights potential limitations, including the risk of over-competition and the need for thoughtful instructional design. Overall, the research concludes that when applied effectively, gamification can significantly enrich English language teaching and contribute to more meaningful learning outcomes.